Flow-through Anterolateral Thigh Flaps: Report of 3 Consecutive Cases and Review of its Utility. Issue 5 (27th May 2021) - Saad, Noah H.; Rosso, Kelly; Wang, Howard; Cromack, Douglas; Karamanos, Efstathios
Abstract : Summary: In the field of plastic and reconstructive surgery, soft tissue reconstruction of Gustilo 3B with peripheral vascular disease or 3C fractures is a complex treatment algorithm. The concomitant issue of soft tissue coverage with vascular reconstruction is the main challenge when opting for free tissue transfer. The flow-through flap offers the surgeon the ability to treat a vascular injury or high-grade stenosis to maintain distal perfusion, while also providing soft tissue coverage. In this study, we present a case series of 3 patients who underwent flow-through anterolateral thigh free flap for lower extremity soft tissue coverage. Each patient had a history of trauma and either single vessel runoff or a dominant branch with diminutive secondary blood flow to the foot. All patients successfully underwent free flap reconstruction of lower extremity wounds while concomitantly reconstructing diseased arterial supply. Only 1 patient suffered partial flap loss postoperatively that was treated with debridement and split thickness skin grafting. Flow-through free tissue transfer is a valuable treatment option not only in Gustilo 3C fractures requiring soft tissue coverage, but also in patients with Gustilo 3B fractures with peripheral vascular disease.